Influences of the insertion method in glass ionomer cement porosity - Da Mata, Margareth [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Cilense Zuanon, Angela Cristina [UNESP] (Wiley-Blackwell, 2012)
The aim of this study was to evaluate the presence of porosities inside the glass ionomer cement (GIC) after different techniques of material insertion. MATERIAL and METHOD: Specimens were prepared with high-viscosity GIC Ketac Molar Easymix and divided into three groups according to the insertion method: spatula (PI), Centrix injector (CI), and low-cost syringe (LCS). The specimens were fractured and observed with scanning electronic microscopy to quantitatively evaluate porosity inside the material using Image J Software. RESULTS: Statistical analysis, ANOVA application, and Tukey test to significance level of 5%, revealed that there was no statistical difference between the groups. CONCLUSION: Although the use of LCS has not decreased the porosity of the material, this insertion method is easy, accessible, and low cost, which makes it a viable alternative of use in the ART technique and in others bucal health programs. Microsc. Res. Tech., 2012. (c) 2012 Wiley Periodicals, Inc.
Keywords: porosity; insertion; glass ionomer cement